2013
DOI: 10.1007/s10911-013-9275-7
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruptors and the Breast: Early Life Effects and Later Life Disease

Abstract: Breast cancer risk has both heritable and environment/lifestyle components. The heritable component is a small contribution (5–27 %), leaving the majority of risk to environment (e.g., applied chemicals, food residues, occupational hazards, pharmaceuticals, stress) and lifestyle (e.g., physical activity, cosmetics, water source, alcohol, smoking). However, these factors are not well-defined, primarily due to the enormous number of factors to be considered. In both humans and rodent models, environmental factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 147 publications
2
99
0
4
Order By: Relevance
“…Breast cancer is the most common gynecologic neoplasia [1,2,3] and the second most frequent cause of death by cancer after lung cancer [2,4,5]. Different genetic and environmental factors influence its development [6].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common gynecologic neoplasia [1,2,3] and the second most frequent cause of death by cancer after lung cancer [2,4,5]. Different genetic and environmental factors influence its development [6].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that they act mainly by an in--vivo mechanism mediated by the estrogen receptor (ER). [11][12][13]21 Although parabens have been termed "weak estrogens" because of their low--binding affinity to the ER, their level of response to the growth of human breast cancer cells in vitro may be the same as that of 17β -estradiol when sufficient concentrations are present. 21 The estrogenic activity of some cosmetic products with parabens has recently been confirmed again by the development of gynecomastia in 3 prepubertal boys as a consequence of the topical application of body oils.…”
Section: -6mentioning
confidence: 99%
“…9 Other potential environmental factors associated with an increased risk of breast cancer are xenoestrogens, chemicals exerting an estrogen-like effect in the body or capable of disrupting the normal metabolism of natural estrogen and thus acting as carcinogens. 11 Currently, there are some 160 xeneoestrogens that may be involved in breast cancer development. Women are the largest group of consumers of cosmetic products, which may be a significant source of xenoestrogens.…”
mentioning
confidence: 99%
“…39 Additionally, more than 100 EDC-related chemicals are widespread mammary carcinogens, 40 and approximately 60 lead directly to tumorigenesis in this tissue. 41 Numerous EDCs, including atrazine, diethylstilbestrol (DES), dibutylphthalate, polybrominated diphenyl ethers, and nonylphenol, were described to interfere with the development of the mammary gland. 42 These substances may alter the growth of this gland, influence gene and protein expression, and cause changes in the numbers of terminal ducts and in histological structure of the breast tissue.…”
mentioning
confidence: 99%
“…41 Prolonged exposure to EDCs may affect the process of mammary gland development by mimicking estrogenic action 45 and influence the prenatal formation of the breast tissue.…”
mentioning
confidence: 99%